Enhanced Eugenol Composition in Clove Essential Oil by Deep Eutectic Solvent-Based Ultrasonic Extraction and Microwave-Assisted Hydrodistillation - Panawan Suttiarporn; Thananan Taithaisong; Samran Namkhot; Suwaporn Luangkamin (Molecules)
Eugenol is the key bioactive compound in clove oil, which has a variety of biological functions and is extensively employed in the medicinal and food industries. Nowadays, deep eutectic solvents (DESs) have received considerable attention as green solvents that enhance extraction efficiency. The present study investigated the effects of DESs on the eugenol composition in clove essential oils (CEOs) extracted from clove buds using ultrasonic- and microwave-assisted hydrodistillation techniques. The study revealed that both DES-based microwave-assisted hydrodistillation (DES-MHD) and ultrasonic-assisted DES pretreatment followed by microwave-assisted hydrodistillation (U-DES-MHD) significantly enhanced the eugenol purity in CEOs compared to the MHD method without the use of DESs. The great CEOs with a high amount of eugenol obtained via choline chloride–oxalic acid (ChCl-OA) at a 1:2 molar ratio were used as DESs. Their oils had a eugenol content of 82.90% and 83.34%, respectively, corresponding to the extraction by DES-MHD and U-DES-MHD methods, which were raised from the oil’s extraction without DES by MHD 7.42% and 8.36%, respectively. Corresponding to a strong antioxidant agent of eugenol, the oils extracted by ChCl-OA-based MHD and ultrasonic-assisted ChCl-OA-based MHD methods had significantly stronger DPPH radical scavenging activity with an IC50 level of 2.16 ± 0.11 and 2.19 ± 0.05 μg/mL, respectively, than the oils extracted without DESs. Hence, these innovative processes offer a promising approach to improving the bioactivity of clove oils, while providing straightforward operation and environmentally friendly extraction methods. Additionally, these novel processes may find application in other edible essential oil extractions for the food and pharmaceutical industries.